Empreendedorismo político no Congresso Nacional brasileiro: a participação da Secretaria de Direitos Humanos na tramitação da PEC do trabalho escravo - Velani, Luís Gustavo (2015)
This paper focuses on the performance of the Republic Presidency Human Rights Secretary (SDH/PR) during the negotiation of the PEC (Constitutional Amendment Proposition) known as Slave Work PEC, which lasted 15 years in the National Congress, and was promulgated in June, 2014, originating Constitutional Amendment 81/14. We hope to be able to contribute to the debate about the role of political entrepreneurs in formulating public policies in Brazil. The long transaction process on the matter and the discrepancies among important sectors of Congress and society constitute a starting point for the investigation of the process of consensus formulation which makes a legislative proposition thrive, and allow identifying the political entrepreneurs (KINGDON, 2011) who were prominent during the process. Interviews and primary and secondary data analyses were the basis for identifying groups more or less organized to pressure the legislative process. Those groups constitute that Sabatier and Jenkins-Smith define as advocacy coalitions, that is, groups which organize around a system of common values and beliefs in order to influence the process of public policies formulation (SABATIER, 1988). The proposition here is to analyze players (NGOs, media, and international organizations) and to understand the way they act and how it was possible to articulate all of those interests, thus expanding academic comprehension about the production of public policies and the impact caused by those “alternative” players in the formulation of the referred law proposition. We were able to verify, along with the SDH/PR’s performance, the conceptual fundaments for policy learning and its performance as political entrepreneur, which was decisive in the approval of Slave Work PEC. Moreover, the SDH/PR was important to what we called “creating decision moments”, a crucial breakthrough in disrupting the procrastination cycle which marked PEC’s transaction history. SDH/PR’s political entrepreneurship went beyond the prerogatives defined by multiple streams framework itself: a Brazilian political entrepreneurship.